DYNAMIC CHARACTERISTICS OF COARSE-GRAINED TRICKLING FILTERS - JERZY SAWICKI; SŁAWOMIRA BERING (TASK Quarterly, 2007)
A structural method of dimensioning trickling filters is proposed. Reactors applied in sanitary engineering are usually designed on the basis of formally simple technical instructions, but laboratory experiments have shown that the flow through a trickling filter can be described with the plug-flow model. With an additional function describing reaction intensity, the object’s parameters can be calculated and its operation simulated for various technical conditions. If variability of the reaction rate is taken into account, numerical integration of the governing equations will be necessary.